In vitro Propagation of Castanea sativa Mill - S A, Zakeri; Hashimah, Elias; N S, Khairul Ikram; K, Othman (2021)
Castanea sativa Mill. (European chestnut) has been recognized as a multipurpose plant, mainly for food, health benefits, timber production etc. Nowadays, it is becoming a staple food in southern Europe, Turkey, southwestern and eastern Asia which made propagation and conservation crucial for sustainability of the plant. Hence, this study was performed to establish the efficient sterilization protocols besides investigate the effects of plant growth regulators and additives either applied singly or in combination on in vitro propagation of Castanea sativa Mill. In vitro propagation is an alternative tool to obtain a good quality mass production rapidly for availability of yields and products throughout the years. In the present study, seeds of Castanea sativa were initially subjected to disinfectant agents for surface sterilization before grown on MS basal. The aseptic seedlings were then excised, cultured in various treatments and eventually maintained in the culture room. Observations recorded including the germination rate (%), Mean number of shoots, roots and leaves produced, Shoot, root and leaves production (%), Shoots, roots and leaves length (cm).